STRATEGI KEPALA MADRASAH IBTIDAIYAH TARBIYATUL ISLAM DALAM MENINGKATKAN NILAI MORAL SISWA CINTA LINGKUNGAN - Ghazali, M. Imam; Ainul Yaqin , Firdaus; Purwantoro , Farich (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies implemented by the principal of Tarbiyatul Islam Elementary School to strengthen students' moral values based on ecological awareness. The background of this study is based on the urgency of internalizing moral values from an early age, particularly environmental awareness as an integral element of character education. The approach adopted was qualitative with a case study design. Data collection was conducted through participatory observation, in-depth interviews, and document analysis, involving the principal, teaching staff, and students as the main subjects. Data analysis followed the Miles and Huberman model, including data reduction, data display, verification, and conclusion stages. The research findings indicate that the strategies implemented by the principal include several main stages, namely the integration of environmental values into the learning process, the formation of environmental awareness habits such as community service and reforestation programs, role models from the principal and teachers, and the strengthening of a school culture oriented towards environmental conservation. These strategies successfully fostered students' caring attitudes, sense of responsibility, and awareness of the environment. Therefore, the role of the madrasah principal is a crucial element in the formation of students' moral values through a consistent, consistent, and sustainable approach.